Narrative Memory Work of Employees in Family Businesses: How Founding Stories Shape Organizational Identification. (March 2023) - Hoon, Christina; Brinkmann, Julia; Baluch, Alina M.
This study is concerned with how founding stories are sustained across multiple generations of employees in family firms and how these stories influence organizational identification. Drawing on a social memory perspective and narrative memory work, we explore the retold founding stories of employees in a large agricultural family firm. Our study demonstrates that founding stories transform firsthand memories into collective memory across multiple generations through intertwining intradiegetic storytelling with material and relational processes. The effortful work of remembering together across familial and social relations, spaces, and embodied ways explains how successive generations understand their belongingness to the organization.